In-vitro antibacterial activity of Zingiber officinale (ginger) against bacteria isolated from reproductive tract of clinical endometritic Murrah buffaloes - SHARMA, PUSHKAR; SRIVASTAVA, SUSHANT; KANT, RISHI; SINGH, BHOOPENDRA; SAURABH (The Indian Journal of Animal Sciences, 2024)
Endometritis, an inflammation of the innermost uterine layer, is caused by a variety of bacteria, including Gram- positive and Gram-negative aerobes and anaerobes. This study aimed to identify the active compounds in Zingiber officinale (ginger) and assess its effectiveness against common bacterial pathogens found in Murrah buffaloes suffering from endometritis. The infrared spectrum of ginger powder displayed a range of wavelengths from 3361.89/cm to 664.26/cm, indicating the presence of eight functional groups. In the hydro-ethanolic ginger extract, the spectrum ranged from 3402.8/cm to 765.35/cm, revealing 12 functional groups. A total of 42 vaginal mucus samples were collected, with E. coli being the most prevalent in 23 samples, followed by S. aureus in 21 samples, Pseudomonas spp. in 12 samples, and Campylobacter spp. in 11 samples. To evaluate the in vitro antibacterial activity of ginger extracts, antimicrobial susceptibility tests were conducted at concentrations of 2.5, 5, 10, 20, 30, 40, and 50 mg/ml. Staphylococcus aureus exhibited the highest sensitivity to the ginger extract, while E. coli showed substantial resistance. In conclusion, ginger demonstrates potent antibacterial activity against multidrug-resistant uterine pathogens and could serve as an alternative therapy to mitigate the risk of drug resistance in treating uterine infections.